LASSO GARZÓN, FREDDY XAVIER - (:unkn) unknown (My University, 2025)
Freddy Lasso Garzón, a professor at the Universidad UTE, is a Tourism Management and Environmental Preservation Engineer who graduated from the same institution. He holds a Master’s in Sciences with a specialization in Environmental Systems from the Instituto Tecnológico y de Estudios Superiores de Monterrey (ITESM, Mexico), and is currently pursuing a Master’s in Food and Beverage Management and Innovation at the Universidad Técnica Particular de Loja (UTPL). As a lecturer, he teaches environmental management, sustainable tourism, and technological innovation. He is the CEO of Air Humming Drone Intelligence, a leading company in intelligent drone applications for environmental monitoring, preservation, and tourism. An expert member of the Ecuador Drone Club at Yachay Tech, he promotes the development of unmanned technologies. Additionally, he serves as a Researcher at the Foundation for Science, Management, and Technology, where he integrates drones with environmental systems to deliver sustainable solutions. His interdisciplinary career combines teaching, business leadership, and applied research, with a focus on environmental preservation and emerging technologies.
Keywords: Hotelería; restaurantes y servicios de banquetes; Viajes; turismo y actividades; Sistema Turístico